2018
DOI: 10.3390/cancers10080263
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Implications of Nonbiological Factors with Staging, Prognosis and Clinical Management in Colon Cancer

Abstract: Background: The present study analyzed the nonbiological factors (NBFs) together with the American Joint Committee on Cancer (AJCC) Tumor-Node-Metastasis (TNM) staging system to generate a refined, risk-adapted stage for the clinical treatment of colon cancer. Methods: Eligible patients (N = 28,818) with colon cancer between 1 January 2010 and 31 December 2014, were identified from the Surveillance, Epidemiology, and End Results (SEER) database. Kaplan-Meier curves and Cox proportional hazards regression, anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 34 publications
(43 reference statements)
2
18
2
Order By: Relevance
“…In our study, this trend was also observed, and the widowed group had the lowest percentage of insurance, which may partly lead to their survival disadvantages. Additionally, it has been pointed that delayed diagnosis could contribute to poor survival among unmarried patients 8,19. However, in our study, incidence of early stage (stage I/II) cancer was higher in the single group (65.2%), divorced (64.8%), and widowed (63.2%) groups, compared with the married (64.1%).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In our study, this trend was also observed, and the widowed group had the lowest percentage of insurance, which may partly lead to their survival disadvantages. Additionally, it has been pointed that delayed diagnosis could contribute to poor survival among unmarried patients 8,19. However, in our study, incidence of early stage (stage I/II) cancer was higher in the single group (65.2%), divorced (64.8%), and widowed (63.2%) groups, compared with the married (64.1%).…”
Section: Discussioncontrasting
confidence: 60%
“…Recently, results from considerable literature have disclosed that that married patients have superior survival compared to the unmarried in various cancers5, such as soft tissue sarcoma6, liver cancer7 and colon cancer8. This interesting phenomenon arise much public attentions.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters of age, gender, race, AJCC stage, examined lymph node count and lymphatic invasion have been identified as important clinicopathological features of COAD prognosis. Specifically, age was found to be the most important prognostic factor for stage II COAD patients [ 13 ], women had a better prognosis than men [ 14 ], whites had a higher colorectal cancer survival rate than blacks [ 15 ], the AJCC TNM staging system was found to be a necessary adjuvant chemotherapy guide for stage II and III COAD patients [ 16 ], the examined lymph node count had excellent prognostic value for COAD patients undergoing surgery [ 17 ] and lymphatic invasion diagnosis was found to be an important indicator of lymph node metastasis in T1 COAD [ 18 ]. Since early-stage patients are more likely to be cured, prognostic markers that can effectively predict the risk of these patients will have higher clinical value [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…One feature of a good prognostic biomarker is its independence from clinicopathological prognostic factors. Clinicopathological characteristics such as age [ 13 ], gender [ 14 ], race [ 15 ], AJCC stage [ 16 ], examined lymph node count [ 17 ] and lymphatic invasion [ 18 ] have been identified as the primary predictors of prognosis in COAD. However, studies of methylated prognostic biomarkers thus far have not produced combined prognostic models based on genome-wide CpG sites that can effectively predict the OS of COAD patients independently of these important clinicopathological characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…We recorded tumor size as a continuous variable. The patients were divided into four size groups of less than 5 centimeters ( ≤ 5 cm), between 5 and 8 centimeters (>5 to 8 cm), over 8 centimeters (>8 cm), or unknown size, according to previous investigations (5, 7, 9).…”
Section: Methodsmentioning
confidence: 99%